Xylan from corn cobs, a promising polymer for drug delivery: Production and characterization - Oliveira, Elquio Eleamen; Silva, Acarilia Eduardo; Nagashima Junior, Toshiyuki; Salgado Gomes, Monique Christine; Aguiar, Larissa Muratori; Marcelino, Henrique Rodrigues; Araujo, Ivonete Batista; Bayer, Marc P.; Ricardo, Nagila M. P. S.; Oliveira, Anselmo Gomes de [UNESP]; Tabosa Egito, Eryvaldo Socrates (Elsevier B.V., 2010)
Although many authors have reported several beneficial effects ascribed to xylan, such as inhibitory action on mutagenicity activity. antiphlogistic effects, and mitogenic and comitogenic activities, few papers have investigated a systematic study on the technological properties of this polymer. The aim of the present work was to evaluate xylan as a promise raw material for the pharmaceutical industry. The water-insoluble xylan samples were extracted from corn cobs following several steps. The obtained powered sample was analyzed by infrared and RMN spectroscopy, and characterized regarding their particle size, bulk and tap densities, compressibility index, compactability, Hausner ratio, and angle of repose. According to the results, infrared and RMN spectroscopy were shown to be able to evaluate the xylan structural conformation and composition, respectively. In addition, rheological data demonstrated that xylan powder obtained from corn cobs may be characterized as a material with low density and very cohesive flow properties. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Xylan; Biopolymer; Fourier transform infrared; Flow properties; Bioresource